Irrigation Buildings, Availability of Irrigation Water, and Water Needs for Rice Plants (Oriza sativa L.): A Review of Wae Bini Irrigation System in Savana Jaya Waeapo, Buru Regency - Ningkeula, Edy Said; F. Assagaf, Sjaid; Saing, Zubair (Agrikan Jurnal Agribisnis Perikanan, 2023)
The amount of water required in a region so that these plants may grow adequately and provide good results is referred to as the requirement for water for agriculture or the need for irrigation. This study used the Cropwat 8.0 software with the Penman-Monteith technique to calculate the water demands of rice plants so that the water requirements of Wae Bini Irrigation could be understood for the development and production of rice plants. This study aimed to evaluate the physical conditions and cropping patterns, as well as the relative irrigation water needs and rice plant productivity. This research may be utilized as an agricultural database and as information for farmers, other researchers, and interested parties, as well as for future agricultural crop growth in Savana Jaya Village, Waeapo District, Buru Regency. The rain efficiency at MT I was 87.1%, and the irrigation schedule efficiency was 67.7%, with an irrigation schedule variance of 0.0%, suggesting that this growing season was optimal for plant development. The rain efficiency at MT-II was 82.0%, and the irrigation schedule efficiency was 64.6%, with an irrigation schedule variance of 0.0%, suggesting that the growing season is favorable for healthy plant development.